Price Discovery and Pricing Choice under Divergent Supply Scenarios in an Experimental Market for Fed Cattle - Clement E. Ward (Journal of Agricultural and Resource Economics, 2005)
Previous research has not addressed the impacts of alternative supply conditions on price discovery and pricing choice. This study estimated models with data from an experimental market, the Fed Cattle Market Simulator, encompassing live weight, dressed weight, and grid pricing under two alternative supply scenarios. Significance of variables explaining transaction price variation and pricing choice differed between the two supply periods. Overall results were close to expectations. Higher quality cattle marketed with a grid brought higher prices in both supply periods. Having lower quality cattle in either supply period increased the probability of cattle being marketed (purchased) on a live weight basis.